Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 50 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Bolitoglossa Duméril, Bibron & Duméril, 1854", "Country is Venezuela (Bolivarian Republic of)" ] } The dataset includes 50 records from 14 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001628-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences